CMM recovery, utilization and cogeneration by compressor plants - Bulat, A.F.; Kirik, G.V.; Zharkov, P.E.; Bluss, B.O.; Shevchenko, V. (Геотехнічна механіка, 2016)
The article presents the designed schemes and compressor plants for degassing coal
beds and utilizing coal mine methane (CMM) and automatic system for controlling their operation.
Interdependence between methane-bearing coal structure, permeability and absorption properties
are analyzed. A model of influence of gases, which differ by their sorption energy, on the coal bed
and possible schemes for intensifying methane recovery from the coal beds are described. A plant
was designed for degassing the underground beds, in which rotary compressor pumps out the gas
mixtures and degases the beds without characteristic formation of crystalline hydrate with methane.
A station was designed for mine gas utilization. A method is proposed for methane recovery, which
assumes pumping of carbon dioxide into the coal bed, which, due to the higher sorption capacity than that of methane, displaces methane adsorbed by the coal. Plants УКГ (Compressor GasUtilizing
Plant – CGUP) were designed for methane utilization and combustion in special chamber
and for preventing methane from escaping into atmosphere, or for feeding it to the equipment for
use in energy sector (production of electricity and heat). The experience on using this technology
and equipment with the view to increase the coalbed methane (CBM) recovery from the coal beds is
presented. Розроблено схеми і установки для дегазації вугільних пластів та утилізації
шахтного метану, а також системи автоматичного керування їх роботою. Проаналізовано
взаємозв'язок структури, проникності та сорбційні властивості вугілля, що вміщають метан.
Запропоновано модель впливу на вугільні пласти газів, що різняться енергією сорбції, і можливі схеми інтенсифікації метановіддачі вугільних пластів. Розроблено установку для дегазації підземних пластів, в якій роторний компресор забезпечує відкачування суміші газів,
унаслідок чого забезпечується дегазація пластів без традиційних для цього процесу явищ
утворення кристалогідратів з метаном. Розроблено станцію для утилізації шахтного газу. Запропоновано спосіб видобутку метану, в якому реалізується накачування у вугільний пласт
вуглекислого газу, що унаслідок більшої сорбційної здатності, чим у метані, витісняє адсорбований вугіллям метан. Розроблено установки для утилізації метану УКГ, що призначені
для спалювання його в спеціальній камері, запобігання цим виділення в атмосферу або його
подачі на устаткування для енергетичного застосування (одержання електрики і тепла). Викладено досвід застосування технологій і устаткування для підвищення метановіддачі вугільних пластів. Разработаны схемы и установки для дегазации угольных пластов и утилизации шахтного метана, а также системы автоматического управления их работой. Проанализирована взаимосвязь структуры, проницаемости и сорбционные свойства угля, вмещающие
метан. Предложена модель влияния на угольные пластов газов, которые различаются энергией сорбции, и возможные схемы интенсификации метаноотдачи угольных пластов. Разработана установка для дегазации подземных пластов, в которой роторный компрессор обеспечивает откачивание смеси газов, вследствие чего обеспечивается дегазация пластов без традиционных для этого процесса явлений образования кристалогидратов с метаном. Разработана
станция для утилизации шахтного газа. Предложен способ добычи метана, в котором реализуется закачка в угольный пласта углекислого газа, который вследствие большей сорбционной способности, чем в метане, вытесняет адсорбированный углем метан. Разработаны установки для утилизации метана УКГ, предназначенные для сжигания его в специальной камере, предотвращения его выделения в атмосферу или его подачи на оборудование для энергетического применения (получение электричества и тепла). Изложен опыт применения технологий и оборудования для повышения метаноотдачи угольных пластов.